The Effects of Self-Confidence and Social Support on Student’s Learning Loss - Muhsin, Muhsin; Puji Sugiharto, Dwi Yuwono; Awalya, Awalya (Universitas Negeri Semarang, 2023)
Difficulties in learning process can cause learning loss. Learning loss is defined as the inability to maximally conduct the learning process at school. This research attempted to prove the effects of self-confidence and social support on learning loss. It used a correlational design and involved 151 students of grade VIII. Findings showed that both self-confidence and social support influenced the decrease in learning loss. Thus, it is suggested to improve students’ self-confidence and social support to reduce the chance of learning loss.